2022
DOI: 10.1007/s00238-021-01934-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical measurements and patients’ perception of excess skin on arms and thighs before and after bariatric surgery

Abstract: Background Bariatric surgery is an effective weight loss method for patients with obesity. One side effect of bariatric surgery is uncomfortable excess skin. Much remains to be learned about physical measurements and patients’ subjective perceptions of it. Here, we investigated the pre- to post-bariatric changes in patients’ perception and physical measurements of the skin on the arms and thighs, in order to find possible subgroups especially affected by post-operative excess skin and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…A better understanding of factors associated with ES quantity post-MBS is essential to help identify patient pre-MBS at risk of greater ES, and prepare them to realistic expectations [8]. In line with prior studies [4,8,29], quantitative and qualitative results suggest maximal BMI, pre-MBS and current BMI, but not psychosocial factors, are related to ES quantity post-MBS. As these findings were retrospective, these results need to be confirmed in prospective longitudinal studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A better understanding of factors associated with ES quantity post-MBS is essential to help identify patient pre-MBS at risk of greater ES, and prepare them to realistic expectations [8]. In line with prior studies [4,8,29], quantitative and qualitative results suggest maximal BMI, pre-MBS and current BMI, but not psychosocial factors, are related to ES quantity post-MBS. As these findings were retrospective, these results need to be confirmed in prospective longitudinal studies.…”
Section: Discussionsupporting
confidence: 63%
“…As a result, methods relying on measured ES (M-ES) quantity are employed. Unfortunately, because few studies have investigated these outcomes together, evidence is lacking to ascertain if Sr-ES and M-ES quantity are associated (and provide evidence of convergent validity), and whether they relate to inconveniences caused by ES [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, according to findings of a study that evaluated the changes following BS in perception and physical measurements of arm and thigh skin and degree of excess skin discomfort, female participants had experienced significantly more excess skin and higher discomfort in the arms than male participants. 26 Furthermore, Biörserud et al 27 and Staalesen et al 23,25 reported a similar finding concerning excess skin and discomfort on several body parts. In this study, the time elapsed since BS correlated negatively and significantly with the desire for BCS; this is in line with prior studies.…”
Section: Discussionmentioning
confidence: 68%